Glycine-arginine-[alpha]-ketoisocaproic acid improves performance of repeated cycling sprints - Buford, B. N.; Koch, A. J. (Medicine & Science in Sports & Exercise, 2004)
Purpose: The purpose of this study was to determine the effect of glycine-arginine-[alpha]-ketoisocaproic acid (GAKIC) supplementation on repeated bouts of anaerobic cycling performance. Methods: Ten men completed a randomized, double-blinded, placebo-controlled exercise protocol of two sessions separated by 7 d. Plasma lactate was analyzed in blood collected 45 min before exercise (REST) and 5 min postexercise (POST). Subjects consumed either 11.2-g GAKIC or placebo (PLC) during a 45-min period between the REST and exercise. Mean power, peak power, and fatigue values were assessed from five supramaximal, 10-s cycle ergometer sprints, separated by 1-min rest intervals. Data were analyzed using repeated measures ANCOVA. Results: A significant treatment x time interaction (P = 0.039) was observed for the change in mean power output over the five sprints between the GAKIC and PLC treatments. Post hoc analyses revealed a greater retention of mean power (P = 0.038) between sprints 1 and 2 after GAKIC (-1 +/- 9 W) versus PLC treatment (-47 +/- 18 W). No other performance variables differed between PLC and GAKIC. POST lactate was increased (P < 0.001) above REST, but there was no difference between treatments (P = 0.936). Conclusion: These data support an ergogenic effect of GAKIC for attenuating the decline in mean power during repeated bouts of supramaximal exercise.